Implications Finance from Use of Weather Derivatives (Derivatives Weather) for Hedging : An Overview Literature about The impact to Cost Energy Company Loans - Seger Santoso; Farah Qalbia (International Journal of Business Law, Business Ethic, Business Comunication & Green Economics, 2024)
This qualitative literature review explores the financial implications of using weather derivatives as a hedging tool to reduce borrowing costs for energy companies. By synthesizing existing studies, the review highlights that weather derivatives significantly lower borrowing costs, with an average reduction of 21 basis points in borrowing rates. This cost-saving effect is more pronounced for companies with higher systematic risk or less complex financial statements. The review also finds that hedging with weather derivatives enhances financial stability and reduces bankruptcy risk, leading to more favorable borrowing terms. Furthermore, the benefits extend to the public debt market, with hedging companies enjoying lower bond yield spreads. Despite making important contributions, the study acknowledges limitations, including reliance on published literature and the need for further empirical validation. Overall, the findings highlight the value of weather derivatives in financial risk management for energy companies.